Lithological constraints on resource economies shape the mycorrhizal composition of a Bornean rain forest. Issue 1 (25th June 2020) - Weemstra, Monique; Peay, Kabir G.; Davies, Stuart J.; Mohamad, Mohizah; Itoh, Akira; Tan, Sylvester; Russo, Sabrina E.
Summary: Arbuscular mycorrhizal fungi (AMF) and ectomycorrhizal fungi (EMF) produce contrasting plant–soil feedbacks, but how these feedbacks are constrained by lithology is poorly understood. We investigated the hypothesis that lithological drivers of soil fertility filter plant resource economic strategies in ways that influence the relative fitness of trees with AMF or EMF symbioses in a Bornean rain forest containing species with both mycorrhizal strategies. Using forest inventory data on 1245 tree species, we found that although AMF‐hosting trees had greater relative dominance on all soil types, with declining lithological soil fertility EMF‐hosting trees became more dominant. Data on 13 leaf traits and wood density for a total of 150 species showed that variation was almost always associated with soil type, whereas for six leaf traits (structural properties; carbon, nitrogen, phosphorus ratios, nitrogen isotopes), variation was also associated with mycorrhizal strategy. EMF‐hosting species had slower leaf economics than AMF‐hosts, demonstrating the central role of mycorrhizal symbiosis in plant resource economies. At the global scale, climate has been shown to shape forest mycorrhizal composition, but here we show that in communities it depends on soil lithology, suggesting scale‐dependent abiotic factors influence feedbacks underlying the relative fitness of different mycorrhizal strategies.